Eosinophilic and Mixed‐Cell Infiltration in Odontogenic Cutaneous Sinus Tracts of a Dog - Sungjae Lee; Jooyoung Park; Yeon Chae; Hakhyun Kim; Taesik Yun; Byeong‐Teck Kang (Veterinary Medicine and Science)
ABSTRACT A 7‐year‐old neutered female Shih Tzu presented with bilateral skin lesions and a subcutaneous mass in the submandibular region. The initial lesion on the right appeared as a plaque, followed by the development of an ulcer on the opposite side 2–3 days later. Despite treatment with antibiotics, antifungal drugs and anti‐inflammatory steroids, lesions persisted. There was an initial improvement with steroids; however, the lesions developed into scars, erythema and papules. A biopsy revealed eosinophilic and mixed‐cell dermatitis requiring treatment with immunosuppressive steroids and cyclosporine, which resolved the plaque and ulcer but only partially reduced the subcutaneous mass. Surgical resection was considered, and subsequent skull radiography revealed alveolar bone loss. During surgery, a sinus tract was identified extending from teeth 309 to 409, indicating that the tissue changes were likely due to drainage from the periodontal disease. Based on clinical history and examination results, the case was definitively diagnosed as an odontogenic cutaneous sinus tract (OCST). Following surgery, no recurrence of the lesion or mass was observed. This is the first case report describing the histopathological features of a submandibular OCST in a dog, highlighting the importance of considering this condition when submandibular lesions do not fully respond to immunosuppressive therapy.